Embedding Indigenous Values in Blue Economy Governance: The Gemohing Cultural Values for Coastal Tourism Development in Mekko, Indonesia - Bidi, Maximianus Ardon; Tokan, Frans Bapa; Gai, Apolonaris; Lamawuran, Yosef Dionisius (Universitas Teuku Umar, 2026)
This study examines the potential integration of the Gemohing cultural values of the Lamaholot community into a blue economy management model in Hamlet III Mekko, Pledo Village, Witihama District, East Flores Regency. Gemohing values, which reflect the spirit of mutual cooperation, deliberation, solidarity, and fair benefit sharing, have historically developed in land-based activities but have strategic relevance for marine and coastal resource management. The research method combines a qualitative approach through literature review, in-depth interviews, and Focus Group Discussions (FGDs) with key stakeholders, including local government, village government, traditional leaders, and the Bajo community. The results show that the Bajo community faces socio-economic challenges such as structural poverty, low access to education, limited institutional capacity, and minimal participation in decision-making. Although Mekko has high ecological and marine tourism potential, its utilization has not been optimal due to weak coordination between stakeholders and limited infrastructure. The proposed Gemohing-based management model positions the community as the main actor through participatory mechanisms, proportional benefit sharing, and cross-sector collaboration, thus potentially improving economic welfare while maintaining the sustainability of the marine ecosystem.